2000
DOI: 10.1023/a:1007526114744
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A novel drug delivery concept based on the encapsulation of liposomes in biodegradable dextran-based microspheres was designed. The system released the liposomes in intact form in a controlled way after a prolonged period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Polymer-based systems, such as hydrogel or prefabricated scaffolds have been used as depots for drugs, regenerative cells, protein, growth factor, and pre-encapsulated drug-loaded liposome for sustained release [8, 12, 8185]. Various polymers have been researched for this application based on their fundamental properties such as biodegradability, biocompatibility, nontoxicity, and the noninflammatory tendency.…”
Section: Temporary Depot Polymeric-based Systems For Liposomal Coumentioning
confidence: 99%
See 2 more Smart Citations
“…Polymer-based systems, such as hydrogel or prefabricated scaffolds have been used as depots for drugs, regenerative cells, protein, growth factor, and pre-encapsulated drug-loaded liposome for sustained release [8, 12, 8185]. Various polymers have been researched for this application based on their fundamental properties such as biodegradability, biocompatibility, nontoxicity, and the noninflammatory tendency.…”
Section: Temporary Depot Polymeric-based Systems For Liposomal Coumentioning
confidence: 99%
“…However, the benefit on sustained release for the pre-encapsulated drug loaded scaffold over a long period of time has been reported and declared successful [96]. Stenekes and coworkers [8] demonstrated that liposome embedded inside a biodegaradble depot polymeric scaffold was able to sustained drug release over a prolonged period of time (Figure 8). In addition, the released liposome was found intact after many days storage within the inside depot polymeric scaffold.…”
Section: Temporary Depot Polymeric-based Systems For Liposomal Coumentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between phospholipids and polymers was firstly utilized in the design of microparticles with core/shell structures and characterized as a form of microencapsulated liposomes [95][96][97]. Polymers such as dextran, chitosan, and sodium alginate were used as capsule materials.…”
Section: Phospholipid-based Core/shell Nanoparticlesmentioning
confidence: 99%
“…This limitation could be overcome by reinforcing CPG beads with liposomes, spherical closed nanostructures composed of lipid bilayers, which can encapsulate active agents within their interior. Liposomes loaded with active agents have been entrapped within several types of polysaccharide gel beads based on alginate, chitosan, and dextran [14][15][16][17][18]. These liposomeentrapped gel beads, compared to gel beads or liposomes alone, showed more sustained patterns of drug release, because active agents are enclosed within compact liposomal membrane and the liposomes are more stabilized within the matrices of gel beads [16,17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%